Neonate with intravenous therapy: a literature review addressed to risk prevention - Morales-Álvarez, Clara Teresita (Universidad de Sonora, 2020)
Introduction: Neonatal intravenous therapy is the most used tool for the relief of several pathologies. This therapy is indispensable to administer drugs, parenteral nutrition, blood products, liquids and electrolytes in ill or critically ill newborns. Therefore, it should be considered as a lifeline, since it results essential for the success of the treatment, and for that reason its care should be meticulous. Objective: Provide an update in the praxis of the neonate intravenous therapy, which allows health care personnel to make assertive decisions in regards to care, and subject to scientific evidence. Methodology: A review of the scientific work was performed in English and in Spanish in scientific and medical databases such as PubMed, Scielo, Lilacs, and Science Direct. Results: 104 articles about topics related to neonate child intravenous and pediatric therapy were found, those which reported concrete data about the analysis population were chosen, and those which only mentioned pediatric population data among their results, were excluded. Conclusions: Available national and international scientific literature allows the health personnel to improve the neonate care in regards to the intravenous therapy, by inviting to the reflection on the risk-free practice, in an informed way, and, consequently, more humane.